Prognostic Value of Inflammation-based Prognostic Scores in Patients with Colorectal Cancer - Afonso, João Pedro Lima; Pereira, Ana; Pereira, Joaquim Costa; Martins, Sandra F. (Journal of Coloproctology, 2021)
Background Anatomopathological staging is the primary method to determine the prognosis of patients with colorectal carcinoma (CRC). However, new tools have been developed that can complement it, such as the analysis of the elevation of systemic inflammatory markers.Objective To evaluate the impact of the elevation of scores based on inflammatory markers (the neutrophil-to-lymphocyte ratio [NLR], the Glasgow Prognostic Score [GPS], and isolated C-reactive protein [CRP]) in the prognosis of patients diagnosed with CRC and submitted to potentially curative surgery in Hospital de Braga, Portugal, between January 1st, 2005, and December 31st, 2010.Methods A retrospective analysis of the data of 426 patients was performed, with a collection of several clinico-pathological variables, as well as the levels of lymphocytes, neutrophils, albumin and CRP, in the pre- and postoperative periods, to apply the different scores to the sample.Results From the analysis of the survival curves, we concluded that patients with increased NLR in the pre- and postoperative periods present a lower cancer-related survival than patients with normal NLR (preoperative period: 93.7 versus 122 months; p < 0.001; postoperative period: 112 versus 131 months; p = 0.002). Patients with increased NLR in the pre- and postoperative periods also had a lower disease-free survival (preoperative period: 88.0 versus 122 months; p < 0.001; postoperative period: 111 versus 132 months; p = 0.002). In addition, increased pre- and postoperative NLR was associated with a higher risk of death due to CRC (preoperatively: hazard ratio [HR] = 2.25; p < 0.001; postoperatively: HR = 2.18; p = 0.003). However, the multivariate analysis shows that only postoperative NLR (ajusted HR = 2.66; p = 0.002) does so independently of the remaining variables.Conclusion Regarding the scores applied to the sample, the NLR was the one that most consistently related to the prognosis of the patients. However, it would be useful to develop a prospective study that could confirm this relationship.
Keywords: colorectal cancer; scores of systemic inflammatory markers; NLR; GPS; CRP